EVALUATION OF EDUCATION AND TRAINING IN MINISTRY OF PUBLIC WORKS AND PUBLIC HOUSING - Avianti, Widiya; Pitaloka, Endang (IJBLE Scientific Publications Community Inc., 2023)
The study aims to evaluate the performance of the Ministry of Public Works and Public Housing Training. Evaluation of training performance needs to be carried out to measure the effectiveness of the training program. The scope of the research area covers the Provinces of North Sumatra, South Sumatra, DKI Jakarta, West Java, DI. Jogjakarta, East Java, South Kalimantan, South Sulawesi and Papua. Measurement includes score improvement of the training participants. This research method is a survey using questionnaires as a research instrument. The data is then processed with pre-test and post-test difference test techniques. The results showed that in general, the increase in the score of training participants in each field and each Training Center significantly shows an increase. The highest pre-test and post-test scores is Training Center Jakarta area. While the pre-test and post-test scores for the highest score is Housing and Settlement Finance Sector.